2017
DOI: 10.1007/s10151-017-1699-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term efficacy and safety of three novel sphincter-sparing techniques for anal fistulae: a systematic review

Abstract: All three techniques appear to be safe and feasible options in the management of anal fistulae, and short-term healing rates are acceptable with no sustained effect on continence. There is, however, a paucity of robust data with long-term outcomes. These techniques are thus welcome additions; however, their long-term place in the colorectal surgeon's armamentarium, whether diagnostic or therapeutic, remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 36 publications
0
29
0
1
Order By: Relevance
“…13 Hiçbiri, fistül tedavisinde altın standart cerrahi yaklaşım olarak evrensel olarak kabul edilmemiştir.…”
Section: Introductionunclassified
“…13 Hiçbiri, fistül tedavisinde altın standart cerrahi yaklaşım olarak evrensel olarak kabul edilmemiştir.…”
Section: Introductionunclassified
“…But in the present case because of highly situated internal opening, even the infant feeding tube was not able to come through the anal opening; instead, it was directed up and we also failed to bring it down even with the help of the inserted index finger per anally. A newer technique to find out the site of the internal opening is video-assisted anal fistula treatment (VAAFT) which is diagnostic as well as therapeutic especially in complex Crohn's perianal fistula [15][16][17]. A recent meta-analysis on VAAFT showed that mean operative time was 42 ± 14.2 min, that the internal opening was identified in 85.7% of patients and that recurrence occurred in 14.2% patients after a median follow-up of 9 months [18].…”
Section: Discussionmentioning
confidence: 99%
“…Dear Sir, Haemorrhoidal disease is the most widespread and ancient proctological disorder [1] and its ideal treatment should be painless, safe, effective and incur minimal cost [2], leading to an early recovery. Patients with Grade III-IV haemorrhoidal prolapse or having failed conservative and outpatient treatments can be considered for excisional haemorrhoidectomy.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Lay open fistulotomy can result in a success rate of up to 100% but this is at the expense of continence, especially in complex fistulas [1]. Recently, several sphinctersaving surgical procedures have been advocated for the treatments of FIA, with acceptable results [2,3]; however, the optimal treatment option continues to be debated. One of these techniques is ligation of the intersphincteric fistula tract (LIFT) that was described by Rojanasakul [4]; it had an initial healing rate of 94.4%.…”
mentioning
confidence: 99%